Peran Guru Pendidikan Agama Islam dalam Penanaman Nilai-Nilai Spiritual untuk Meningkatkan Moral Santri - Helmi, Moh.; Amini, Izzat (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This research is motivated by the researcher’s concern regarding the spiritual values of students in the current millennial era. Students have been influenced by culture and technological developments to such an extent that spiritual character values are becoming increasingly distant from their lives, especially in matters related to religion. This thesis discusses the inculcation of spiritual values by Islamic education teachers in improving the morals of santri (Islamic boarding school students). This study employs a descriptive qualitative approach and was conducted at Al-Muqri Islamic Boarding School in Prenduan. The data were obtained from teachers and students of Al-Muqri Prenduan. The data collection techniques used were observation and interviews. Data processing and analysis were carried out in four stages: data collection, data reduction, data presentation, and conclusion drawing. The validity of the data was tested through four criteria: credibility (prolonged engagement, increased persistence, and triangulation), transferability, dependability, and confirmability. The results of the study indicate that: (1) The spiritual values of the students at Al-Muqri Prenduan are generally good; however, aspects related to self-confidence and religious commitment are still lacking and need improvement. (2) The inculcation of spiritual values by Islamic education teachers is carried out through habituation and by providing advice.